Current thinking and scientific ideas on the pathology of Ewing's sarcoma and PNET (International Journal of Food and Nutritional Sciences, 2022)
Small round cell tumours that demonstrate varied degrees of neuroectodermal differentiation are what are known as Ewing's sarcoma and PNET, respectively. They are one of the most frequent tumours to develop in children and can take place in the bone or in the soft tissues. In the past, diagnosis could be accomplished through the use of light microscopy in conjunction with immunohistochemical stains. But nowadays, translocation analyses are being used not only for the diagnosis and classification of small round cell tumours, but also to determine the significance of their prognosis, detect micrometastasis, and monitor minimal residual disease, all of which have the potential to be treated with targeted therapies. In this essay, the author examines the clinical and therapeutic implications of the pathology, biology, and molecular features of Ewing's sarcoma and PNET.